2015
DOI: 10.2169/internalmedicine.54.3092
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Chronic Kidney Disease in Non-Obese Individuals with Clustering of Metabolic Factors: A Longitudinal Study

Abstract: Objective The impact of the clustering of metabolic factors on chronic kidney disease (CKD) in non-obese individuals remains unclear. Methods We conducted a follow-up study of 23,894 Japanese adults (age, 18-69 years) who continuously received annual health examinations between 2000 and 2011. Obesity, high blood pressure, high triglycerides, low high-density lipoprotein (HDL) cholesterol and high fasting blood sugar were defined as metabolic factors, and CKD was defined as renal dysfunction (estimated glomerul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…[81][82][83] A total of 66 studies, comprising 699 065 CKD patients and 11 109 003 participants, were finally included in the meta-analysis. Among the included studies, 43 were from the East Asian populations 8,9,[22][23][24][25][27][28][29]33,[35][36][37][38][39][40][41]43,44,51,52,[55][56][57][58][59]62,[65][66][67]69,[71][72][73][74][75][76][77][78][79][80]82,83 and 23 were from non-East Asian populations. 12,20,21,26,[30...…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…[81][82][83] A total of 66 studies, comprising 699 065 CKD patients and 11 109 003 participants, were finally included in the meta-analysis. Among the included studies, 43 were from the East Asian populations 8,9,[22][23][24][25][27][28][29]33,[35][36][37][38][39][40][41]43,44,51,52,[55][56][57][58][59]62,[65][66][67]69,[71][72][73][74][75][76][77][78][79][80]82,83 and 23 were from non-East Asian populations. 12,20,21,26,[30...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The relationship between HDL-cholesterol level and CKD risk was examined in 45 studies, 9,12,21,23,24,[26][27][28][33][34][35][36][38][39][40]42,44,48,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][67][68][69][71][72][73][74][75][76]79,82,83 including 692 780 patients and 11 039 480 participants. In the overall analysis, the risk estimate for lower values of HDL-cholesterol, as compared with higher values, was 1.20 (95% CI = 1.11-1.30).…”
Section: Reduced Hdl-cholesterolmentioning
confidence: 99%
“…Another study revealed that aging, angina pectoris, and peripheral vascular disease served as predictors of hospitalization [25]. CKD patients are considered to be more likely to (1) have high prevalences of comorbidities (e.g., hypertension and diabetes) whose management is complex [4,11,13,26], (2) have high occurrence and recurrence rates of CVD, acute kidney injury, and infectious diseases [16,17], and (3) develop procedural accidents during hospitalization [27], which may be associated with an increase in the risk of hospitalization, particularly that of long-term hospitalization.…”
Section: Rate Ratiomentioning
confidence: 99%
“…Thus, opportunities to identify CKD are limited. As suggested by recent studies conducted in Japan [14,26], GFR measurement should be widely conducted for more individuals, especially for those at high risk of CKD, in clinical practice and mass health examinations.…”
Section: Rate Ratiomentioning
confidence: 99%
“…Taiwan had the highest prevalence of end-stage renal disease (ESRD) in the world for more than a decade [1]. The prevalence of chronic kidney disease (CKD) is higher in older adults and reached 37.2% in elderly patients (age ≥ 65 years), while the prevalence of CKD is 11.93% in adults of all ages (age ≥ 20 years) in Taiwan [2]. Treatments for CKD have the greatest effects on slowing the rate of disease progression when started early.…”
Section: Introductionmentioning
confidence: 99%